The coupling of perfectly conducting and impedance coaxial waveguides - Büyükaksoy, Alinur; Tayyar, Ismail Hakki; Hacivelioğlu, Feray; Uzgören, Gökhan (My University, 2007)
In the present work a matrix Wiener-Hopf equation connected with the scattering of the dominant TEM mode at the junction of a two-part coaxial waveguide is solved and the influence of the inner and outer cylinders radii and the surface impedances on the reflection and transmission coefficients are presented. © 2007 IEEE. © 2008 Elsevier B.V., All rights reserved.
2007 International Conference on Electromagnetics in Advanced Applications, ICEAA'07 -- Torino -- 72484
Keywords: Coaxial waveguide; Scattering; Wiener-hopf technique